2019
DOI: 10.3390/polym11081302
|View full text |Cite
|
Sign up to set email alerts
|

Improving Oxygen Permeability and Thermostability of Polycarbonate via Copolymerization Modification with Bio-Phenol Polysiloxane

Abstract: As a new kind of functionalized polysiloxane with chemical reactivity, bio-phenol polysiloxane was synthesized through facile heterogeneous catalytic route. Bio-phenol polysiloxane/polycarbonate (Si/PC) block copolymer was synthesized via a three-step approach, and the effect of the amount of bio-phenol polysiloxane on the properties of Si/PC copolymer was then studied. The structure and morphology of Si/PC copolymer were characterized, showing that, when the amount of bio-phenol polysiloxane reached 20%, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Si-PC (Mw = 30,314 g/mol) was synthesized in our laboratory and the mass fraction of eugenol polysiloxane was 10 wt% [13]. Graphene nanoparticle was purchased from Changzhou Sixth Element Material Technology Corporation and the specific surface area of graphene nanoparticle was 160-240 m 2 /g and the particle size was less than 10 um.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Si-PC (Mw = 30,314 g/mol) was synthesized in our laboratory and the mass fraction of eugenol polysiloxane was 10 wt% [13]. Graphene nanoparticle was purchased from Changzhou Sixth Element Material Technology Corporation and the specific surface area of graphene nanoparticle was 160-240 m 2 /g and the particle size was less than 10 um.…”
Section: Methodsmentioning
confidence: 99%
“…Eugenol is a common bio-phenol in the chemical synthesis, and eugenol polysiloxane was used in the polymer modification for its chemical reactivity, antibacterial property and benzene ring which could improve the rigidity of polymer [7][8][9][10][11]. Eugenol pysiloxane-polycarbonate (Si-PC) copolymer was synthesized via copolymerization between eugenol polysiloxane and PC monomer, and thusm reduced the melt viscosity, improved the toughness and improved the thermal properties of PC [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…While antioxidant molecules have been previously grafted onto silicones, antioxidant efficacy was not measured. In most reports of eugenol silicones, for example, eugenol is typically first grafted via hydrosilylation of the allyl group, and then modified with further reactions that block the phenol group, for example, in polyurethanes, 16 ether sulfones, 17 or polycarbonates, 18,19 or as crosslinkers for silicone 20 or other networks. 21 Eugenol-modified silicones in which the phenols are free can exhibit anticorrosion 22 or antibiotic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Their thermal stability, mechanical properties, and hydrophobic properties were significantly improved by increasing the biophenol polysiloxane content. [23,24] There are scattered reports of the use of this biophenolic polysiloxane in other polymers, but there has been no report of its use in the modification of biodegradable materials. Our previous work observed that adding a small amount of biophenol polysiloxane improved the substrate's gloss, enhanced the surface smoothness and scuff resistance properties, and offered a leather-like feel with an enhanced user experience.…”
Section: Introductionmentioning
confidence: 99%